Consumers’ Attitude on Purchase Behavior of Green Products (Pravaha, 2023)
This study aims to investigate the influence of consumers' attitudes on their purchasing behavior toward green products in Nepal. Using a cross-sectional research design, quantitative data were gathered from 240 consumers in the Chitwan district, aged 20 to 40, through a purposive sampling method. Structural Equation Modeling (SEM) analysis reveals that the value consumers place on green consumption has a significant positive impact on their attitude toward green products, as well as their reasons for and against purchasing them. However, an insignificant negative relationship was observed between the reasons for and against purchasing green products and attitudes toward green products. Additionally, attitudes toward green products were found to have a substantial impact on purchasing behavior. The findings emphasize the potential for aligning consumer preferences with environmental sustainability, creating a win-win situation that not only meet their desires but also contribute to a sustainable environment.